Dose Dependent Impact of Dominant Seedborne Fungi on Seed Germination and Seedling Vigour of Cotton Seeds - R. KAVITHA; S. UMESHA; H.S. SHETTY (Seed Research, 2026)
Thirty cotton genotypes belonging to Varalakshmi, Jayalakshmi, DCH-32 and RCH-32 were collected from the three different agro climatic zones of Karnataka state, India. All the collected seed samples were manually delinted and subjected to standard blotter method to screen the seedborne fungi. The dominant seedborne pathogenic fungi were identified and multiplied on potato dextrose agar media. Seeds were artificially treated with all the dominant seedborne fungi. Fungal concentration was assessed using Haemocytometer. Such artificially treated seeds were subjected to seed germination and seedling vigor. All the dominant seedborne fungi reduced seed quality parameters significantly (p=0.05), over their untreated counterparts. However, the effect of these seedborne pathogenic fungi is dependant on fungal dosage. Increased fungal concentration recorded more reduction in seed quality parameters. But the fungal dosage beyond 150-200 x 10 CFUgm did not vary significantly (p=0.05). Among the fungi tested, the highest reduction of seed quality parameters recorded from Verticillium dahliae followed by Myrothecium roridum; Macrophomina phaseolina and Fusarium species.